The Role Of Entrepreneurship Education In Increasing Students' Interest, Creativity, And Entrepreneurial Ability: An Empirical Study On Batam Higher Education - Yopi Yopi; Helprida Simamora; Heryenzus Heryenzus (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
his study aims to examine the role of entrepreneurship education in enhancing students entrepreneurial interest creativity and entrepreneurial abilities at universities in Batam. The research is motivated by the relatively high open unemployment rate in Batam which reached 8.14 percent in early 2024 despite the city strong potential as an industrial and commercial hub. A mixed method approach was employed combining quantitative and qualitative data. Quantitative data were collected through a survey of 200 university students and analyzed using Structural Equation Modeling Partial Least Squares. Qualitative data were obtained from in depth interviews with lecturers and students and analyzed using thematic analysis. The findings indicate that entrepreneurship education has a significant positive effect on entrepreneurial interest creativity and entrepreneurial ability. Qualitative results further highlight the importance of project based learning the involvement of industry practitioners and the presence of campus business incubators in strengthening students creativity and entrepreneurial skills. This study concludes that entrepreneurship education not only fosters entrepreneurial interest but also enhances students creativity and practical entrepreneurial competencies.